“You Never Exhale Fully Because You're Not Sure What's NEXT”: Parents' Experiences of Stress Caring for Children With Chronic Conditions - Smith, Stephanie; Tallon, Mary; Clark, Carrie; Jones, Lauren; Mörelius, Evalotte (Frontiers in Pediatrics, 2022)
Children with chronic conditions are experiencing improved survival worldwide, and it is well-known that their parents are stressed. Yet, despite this knowledge, parents continue to experience stress. Our study explored the lived experience of parental stress when caring for children with various chronic conditions to identify opportunities to potentially reduce stress for these parents. This was an exploratory qualitative study using semi-structured interviews. To ensure appropriate research priorities were addressed, the study was co-designed with consumer and stakeholder involvement. Twenty parents were interviewed. Parents were recruited through a recognized family support organization for children with various care needs in Western Australia. Interviews were audio-recorded, transcribed verbatim, anonymized, and analyzed using Interpretative Phenomenological Analysis. Two superordinate themes were identified: 1) Gut instinct to tipping point included parents as unheard experts and their experiences of stress and becoming overwhelmed. 2) Losses and gains covered the parents’ identity and relationship challenges and coping strategies with their children’s unpredictable conditions. Parents’ experiences of stress caring for children with chronic conditions can be applied to the Job-Demand Control-Support Model for occupational stress. Not only does this application provide a useful framework for practitioners but it adds a unique perspective that reflects the dual role of parents in caring for their children with chronic conditions as a parent but also a professional with a 24/7 workload. The parents’ experiences highlight a need for improved support access, effective communication between parents and health care professionals, discharge preparation and information provision, and regular screening of parental stress with a referral pathway.